Selecting packaging material for dry food products by trade‐off of sustainability and performance: A case study on cookies and milk powder. Issue 5 (22nd February 2021) - Baele, Maarten; Vermeulen, An; Adons, Dimitri; Peeters, Roos; Vandemoortele, Angelique; Devlieghere, Frank; De Meulenaer, Bruno; Ragaert, Peter
Abstract: Alternative packaging concepts for two dry, shelf‐stable food products were evaluated. A trade‐off between recyclability (monolayer materials) and performance (multilayered high‐barrier materials) was made for the packaging materials. Caramellized cookies were packaged in flowpacks made of PP film (OTR 1307 cc/m 2 /d, WVTR 5 g/m 2 /d), acryl‐coated PVdC/PP film (OTR 21.8 cc/m 2 /d, WVTR 4.2 g/m 2 /d) as a reference material and metallized PP (MPP) film (OTR 31.2 cc/m 2 /d, WVTR 0.4 g/m 2 /d) and stored at 22°C and 50% relative humidity. Texture was compromised after 6 months of storage for the former two materials, while the latter provided an extension of textural acceptability. Whole milk powder was packaged in unsealed PE bags as a reference, representing a typical paper bag with a PE liner that is stapled shut without a seal. Alternative packages were sealed PE bags (OTR 1464 cc/m 2 /d, WVTR 3 g/m 2 /d), PE/PA/EVOH/PA/PE (OTR 0.25 cc/m 2 /d, WVTR 0.95 g/m 2 /d) and PA/EVOH/PA/PE (OTR 1.24 cc/m 2 /d, WVTR 8 g/m 2 /d) multilayer bags, and PP/Al/PE (OTR 0.1 cc/m 2 /d, WVTR 0.1 g/m 2 /d) bags and stored at room temperature and relative humidity between 70% and 90%. Unsealed bags were found to be unacceptable for storage at high humidity, due to excessive caking, discolouration and mould growth. Sealed PE bags provided adequate protection against moisture, yet not against oxygen ingress, leading to oxidative off‐odours. The barrier efficiency of PA/EVOH/PA/PE was compromised by the high humidity. Both PE/PA/EVOH/PA/PE and PP/Al/PE bags provided adequate protection for over a year. Abstract : The effect of a typical reference and some alternative packaging materials on the shelf life of two shelf‐stable products, cookies and milk powder, was evaluated. Cookies were packaged in PP film, acryl‐coated PVdC/PP film and metallized PP film. Moisture content and texture evolution in the different materials were evaluated. Milk powder was packaged in unsealed PE bags, sealed PE bags, two multilayer bags and an aluminium laminate bag. Moisture content, lipid oxidation and colour were monitored.